Sacred Feminine: A Decolonial Reading of the Indus Mother Goddess and Gandhara Hariti - Jalil Khan (Elkuator Research and Publication, 2026)
This article examines the colonial and patriarchal framing of female divinities in South Asian archaeology, using two case studies: the Indus Valley Mother deity figurines and the Gandhara deity Hariti. Both types of artifacts, which are currently housed in prominent European institutions such as the British Museum, and the Metropolitan Museum of Art, were often overlooked in colonial scholarship and museum catalogues. While the Mother Goddess figurines were reduced to rudimentary